Development of a Board Game to Promote Learning about Investment in Basic Business Course for First-Year Vocational Certificate Students - มหาชยานนท์ ชนัญชิดา; เรืองชัง นิจจารีย์; ศรีจันทร์ อินทิรา; แย้มชุติ นภวรรณ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 15, 2025)
This research aimed to 1) develop a board game to promote learning about investment with an efficiency of 80/80, 2) compare the learning achievement on investment of students before and after learning with learning activities using board games, and 3) study the satisfaction of students towards learning with learning activities using board games. The sample group consisted of 50 first-year vocational certificate students of Eastern Technological College (E.Tech), BMK. 1/5 room, selected by cluster sampling. The research instruments consisted of 1) board games, 2) learning management plans, 3) achievement tests, and 4) satisfaction questionnaires. The statistics used for data analysis were mean, standard deviation, media efficiency test (E1/E2), and t-test Dependent. The research results found that 1) the board game to promote learning about investment had an efficiency of E1/E2 equal to 80.30/80.13, higher than the efficiency criteria of 80/80. 2) Students who learned with learning activities using board games The post-learning achievement scores (Mean = 24.04, S.D.= 2.63) were significantly higher than those before learning (Mean = 15.24, S.D.= 4.21) at a statistical significance level of .05. 3) Students had the highest overall satisfaction with learning through learning activities using board games (Mean = 4.59, S.D.= 0.56).